Effect of Cadmium-Tolerant Rhizobacteria on Growth Attributes and Chlorophyll Contents of Bitter Gourd under Cadmium Toxicity - Zafar-Ul-Hye, Muhammad; Naeem, Muhammad; Danish, Subhan; Khan, Muhammad Jamil; Fahad, Shah; Datta, Rahul; Brtnicky, Martin; Kintl, Antonin; Hussain, Ghulam Sabir; El-Esawi, Mohamed A (Plants (Basel, Switzerland), 2020)
Cadmium (Cd) is one of the heavy metals that negatively affects the growth of plants. High solubilization in water leads Cd to enter into plants quite easily, thus decreasing seed germination, photosynthesis, and transpiration. It also shows an antagonistic effect with many of the plants' nutrients like Mn, Ca, K, Mg and Fe. Nowadays, inoculation of plants with ACC deaminase (ACCD) rhizobacteria to mitigate Cd's adverse effects has drawn the attention of environmental microbiologists. The rhizobacteria secrete organic compounds that can immobilize Cd in soil. Therefore, this study was accomplished to investigate the effect of ACCD plant growth promoting rhizobacteria (PGPR) on the bitter gourd under Cd stress. There were six treatments consisting of two ACCD PGPR (Stenotrophomonas maltophilia and Agrobacterium fabrum) strains and inorganic fertilizers at two levels of Cd, i.e., 2 (Cd2) and 5 mg kg-1 soil (Cd5). The results showed A. fabrum with the recommended NPK fertilizer (RNPKF) significantly increased the vine length (48 and 55%), fresh weight (24 and 22%), and contents of chlorophyll a (79 and 50%), chlorophyll b (30 and 33%) and total chlorophyll (61 and 36%), over control at the two Cd levels i.e., Cd2 and Cd5, respectively. In conclusion, the recommended NPK fertilizer + A. fabrum combination is a very effective treatment with which to immobilize Cd in soil for the improvement of bitter gourd growth.
Keywords: Momordica charantia; heavy metal; productivity; pigments; mineral fertilizers; PGPR